Estetização e emancipação: as possibilidades éticas da pós-modernidade segundo Gianni Vattimo - Araújo, Filipe Silveira de (2012)
This paper intend to explicit, among main works of Gianni Vattimo, the possibilities, in the Post-Modernity, of thinking a emancipation; maybe not that emancipation of Modernity, whose basis was progress, reason, science. Maybe in Post-Modernity we have an emancipatory project that conceives only a “taking the word” of cultures and subcultures renegade by traditional historical process, that was centered in only one ideal: European modern human. Thus, we can talk about how History, while current unitary, came to an end. The reflections from the end of this unity of history are visible in various forms in the present culture; however, the overall process of aestheticization of life certainly means, more evident, the value pluralist today. The general aestheticization of life is not so much “super-aesthetics”, a unique aesthetics that encompasses all the meaning and values, but a multiplicity of aesthetics values, the most varied, that travel the world through sounds and images as objects of information. Hence some relevance characteristic of mass media: apart from a totalitarian cultural component type-approval, the media represent – despite still abide to certain interests of market – a form of mediation between the different cultural “dialectics”, providing a true “adventure of difference”.